2010
DOI: 10.3109/s10165-009-0245-2
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP response element-binding protein is implicated in IL-6 production from arthritic synovial cells

Abstract: Overproduction of interleukin (IL)-6 from synovial cells is critically involved in the pathogenesis of rheumatoid arthritis (RA). Cyclic adenosine monophosphate (AMP) response element-binding protein (CREB), a leucine zipper transcription factor, is expressed at a high level in synovial cells of patients with RA. Although CREB transactivates IL-6 expression in vascular smooth muscle cells, the relation between CREB expression and IL-6 production from arthritic synovial cells remains unclear. In this study, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…They cooperate to recruit CBP at the IL‐6 promoter, thus enable synergistic gene activation. In consistent with previous reports [Miyazawa et al, 1999; Bergamaschi et al, 2006; Ishizu et al, 2010; Spooren et al, 2010], IL‐1β stimulation led to evident phosphorylation of CREB in FLS from AA rats, NOR showed notable inhibition of it. On the other hand, CREB is a phosphorylation substrate for diverse protein kinases (PKs), such as PKA, PKC, p38 MAPK, and others.…”
Section: Discussionsupporting
confidence: 92%
“…They cooperate to recruit CBP at the IL‐6 promoter, thus enable synergistic gene activation. In consistent with previous reports [Miyazawa et al, 1999; Bergamaschi et al, 2006; Ishizu et al, 2010; Spooren et al, 2010], IL‐1β stimulation led to evident phosphorylation of CREB in FLS from AA rats, NOR showed notable inhibition of it. On the other hand, CREB is a phosphorylation substrate for diverse protein kinases (PKs), such as PKA, PKC, p38 MAPK, and others.…”
Section: Discussionsupporting
confidence: 92%
“…VIP decreased both gene expression and production of TNFα and IL‐6 in synovial tissue and FLS from RA patients (Juarranz et al, 2004). Moreover, CREB protein is also implicated in IL‐6 production from arthritic synovial cells (Ishizu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several papers reported that the activated cAMP/CREB signaling pathway could enhance the IL10 production in human monocytes, and IFN-gamma suppressed IL10 synergize by regulating CREB/AP-1 protein expression [10,11] . CREB is expressed at a higher level in the synovial cells of patients with RA, and it is implicated in IL6 production from synovial cells [12] . However, whether the methylation status of a single CpG site in the IL10 promoter can regulate its transcription through affecting CREB's binding to this region in RA remains unclear.…”
Section: Introductionmentioning
confidence: 99%